Tetra-μ-chlorido-bis(18-crown-6)platinum(II)dipotassium(I) - Ravindran Durai Nayagam, B. (International Union of Crystallography, 2010)
In the title compound, [K(2)PtCl(4)(C(12)H(24)O(6))(2)], the Pt(II) ion is located on an inversion centre and is coordinated by four Cl atoms, forming a square-planar geometry. The K(I) ion is coordinated by six O atoms of the crown ether and two bridging Cl atoms. The K(I) ion is displaced by 0.756 (2) Å from the mean plane of the six O atoms of the crown ether. The molecules are connected by weak C—H⋯O hydrogen bonds, forming an infinite two-dimensional network parallel to the (10[Image: see text]) plane. Intra- and intermolecular C—H⋯Cl hydrogen bonds are also observed.